Հայոց եղեռնը Մաղաքիա Օրմանեանի խոհագրութեան եւ Հրանտ Մաթեւոսեանի ստեղծագործութեան մէջ - Գրիգորեան, Վաչագան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены идеи, поднятые в трудах архиепископа Магакии Орманяна, Гранта Матевосяна и Левона Хечояна, касающиеся геноцида начала XX века. В труде «Раздумья и заветы» Орманян показывает те вопиющие упущения партий того времени, в следствие которых наши потери достигли катастрофических масштабов. Художественное осмысление этих событий было представлено в произведениях Гранта Матевосяна («Нейтральная зона») и Левона Хечояна («Черная книга, тяжелый жук»). Победы над злом можно достигнуть только единой, всеобщей борьбой. The article presents the ideas raised in the writings of Archbishop Malachia Ormanian, Hrant Matevosyan and Levon Khechoyan regarding the Armenian Genocide that took place in the early 20th century. In the book “Thoughts and Words”,Ormanian shows those glaring omissions made by the parties of the time, because of which our losses reached catastrophic proportions. The fictional interpretation of these events was presented in the works of Hrant Mattheosyan (“Neutral Zone”) and Levon Khechoyan (“Black Book, Heavy Beetle”). In the fight against evil, only a unified struggle can be crowned with victory.
Keywords: Armenian Genocide (1915)